Brandis the Forgotten Botanist. (1st November 2021) - Mann, Michael; Schultz, Matthias
Generally, Dietrich Brandis is remembered as the first Inspector General of Forests in British India. However, before he left Europe, he had a university education as a biologist and botanist as well as geographer. After various affiliations with the University of Bonn he became Forest Inspector of Burma through his wife's connections with the British Indian imperial administration. Despite his groundbreaking work as a forester, Brandis however never stopped working as a botanist. The Herbarium Brandis, since his death kept at the University of Hamburg as part of the botanical collections, comprises more than 19, 000 sheets. It is one of the most comprehensive collections on South Asian flora. This article tries to highlight Brandis' role as a botanist.